Reward Dysregulation and Mood Symptoms in an Adolescent Outpatient Sample - Gruber, June (J Abnorm Child Psychol, 2013)
Research on bipolar spectrum disorders (BPSD) in adolescence has burgeoned in the last decade, but continued work is needed to identify endophenotypic markers associated with illness onset and course. The present study examined reward dysregulation – measured via the behavioral activation system (BAS) – as one putative marker of BPSD in adolescence. A diverse group of 425 outpatient adolescents between 11–17 years of age (52% male) completed the Behavioral Inhibition and Activation Scale (BIS-BAS) scale to measure reward dysregulation. Semi-structured interviews determined diagnoses and severity of mood symptoms. Parent-reported BAS was associated with increased symptoms of mania, and parent and adolescent-reported BAS were associated with symptoms of depression. Parent-reported BIS scores were associated with increased symptoms of mania. Results held independent of diagnostic status. Furthermore, parent BIS/BAS reports were stronger predictors for manic symptoms compared to adolescent-reports. Results extend work in adults with BPSD, suggesting a transdiagnostic association between reward dysregulation and mood symptom severity in adolescence.